Lipodystrophy and metabolic parameters of people living with HIV - Menezes, Labibe do Socorro Haber de; Reis, Khayro Lima dos; Sousa, Michel Douglas Silva de; Gonçalves, Diego de Aviz; Rocha, Manfried Cleiton Mendes; Libonati, Rosana Maria Feio (Brazilian Journal of Sexually Transmitted Diseases, 2018)
Introduction: Since the earliest reported cases in the United States, Acquired Immunodeficiency Syndrome (AIDS) remains one of the major challenges to global health. Objective: To evaluate the metabolic parameters and clinical manifestations of lipodystrophy in patients with lipodystrophy syndrome associated with the use of antiretroviral therapy. Methods: A cross-analytical study carried out from December 2015 to June 2016, in a public reference hospital for the care of HIV patients, in the city of Belém, state of Pará, Brazil. The sample consisted of HIV positive serology patients in treatment with antiretrovirals and lipodystrophy. Interviews were conducted and a research protocol plus laboratory analysis applied. Results: A total of 54 patients was included, 68.5% male and 31.5% female, aged 26–72 years, average of 53.07 years (standard deviation — SD±10.41). Among the clinical forms of lipodystrophy, the mixed one was the most prevalent (72.2%). As for dyslipidemia, 30.8% of the patients presented isolated hypertriglyceridemia, 26.9% mixed dyslipidemia, 19.2% low high-density lipoprotein (HDL-c) and 17.3% without dyslipidemia. Regarding the glycemic profile, 28.3% of the patients were diabetic, 28.3% had altered fasting glycaemia and 5.6% had altered fasting glycaemia and glucose intolerance. Conclusion: The clinical form of mixed lipodystrophy was the most prevalent. In this study, there was no association between the lipid profile and the clinical forms of lipodystrophy. However, follow-up of these patients is necessary to avoid possible complications and risks of cardiovascular events.